Exploring bufferless iron speciation in seawater by Competitive Ligand Equilibration-Cathodic Stripping Voltammetry: Does pH control really matter? - Sanvito F.; Monticelli D. (Talanta, 2021)
Iron speciation in seawater is of the utmost importance as this element plays a central role in the regulation of primary productivity. Here we present the development of a CLE-CSV (Competitive Ligand Equilibration-Cathodic Stripping Voltammetry) procedure for iron speciation in seawater avoiding for the first time the use of the pH buffer (2,3-dihydroxynaphthalene is used as the added ligand, atmospheric oxygen as the catalytic enhancer and a 1 mL volume per sample aliquot). The unbuffered method was setup, validated by using known ligands and finally applied to the analysis of six seawater samples from the Ross Sea (Antarctica). The validation procedure demonstrated that ultratrace levels of ligands may be reliably determined and the application to seawater samples proved that the complex natural ligand pool can be detected with results undistinguishable from the ones obtained by the buffered procedure. The proposed method demonstrated a new principle in trace element speciation analysis by CLE-CSV, namely that the equilibration step may be performed at natural pH, whereas the pH may be set at its optimal value for sensitivity during analysis, thanks to the raise in pH at the electrode/solution interface caused by oxygen reduction. This change in paradigm paves the way to the investigation of iron speciation at natural pH in traditionally difficult samples that show circumneutral or slightly acidic pH values. The relevance of the here proposed approach to existing speciation procedures by CLE-CSV is also discussed.